Prophecy and public affairs in later medieval England - Coote, Lesley A. (Lesley Ann), 1954- (York Medieval Press in association with Boydell Press, 2000)
In the first general survey of political prophecy in medieval England for almost a hundred years, Lesley Coote examines the nature of political prophecy, its audience and its reception, from its emergence in the twelfth century to the end of the middle ages. Working from original manuscripts, she reveals prophecy to have been a major language for the discussion of public affairs, enshrining ideas of 'Englishness' and a 'national' community, and introducing a great crusading hero-ruler, a second Arthur, who would lead his people into the Last Days.